The effect of culture-based mathematics learning instruction on mathematical skills: a meta-analytic study - Zuliana, Eka; Dwiningrum, Siti Irene Astuti; Wijaya, Ariyadi; Hukom, Julham (Intelektual Pustaka Media Utama, 2025)
Culture-based mathematics learning (C-bMLI) has emerged as a promising approach to improving students' mathematical skills, yet previous research presents inconsistent findings regarding its efficacy compared to conventional methods. To address this gap, a meta-analytic study is needed to consolidate and present the latest insights regarding the impact of C-bMLI on students' mathematical skills. It also aimed to discern the factors influencing the effectiveness of C-bMLI implementation. Datasets were collected from primary studies published in internationally recognized journals or proceedings. By rigorously adhering to inclusion criteria, a collection of 45 effect sizes from 25 primary studies was identified. The results of this analysis, conducted using the random-effects approach, produced a substantial combined effect size of and . The evidence unequivocally substantiated that the employment of C-bMLI significantly contributed to the mathematical process, standing as a superior alternative to conventional learning methodologies. The results of the heterogeneity analysis of the moderator variables showed that factors such as the type of skills, educational tiers, country, publication year, and the variant of C-bMLI contributed to the observed variance, The variable of sample size did not exert a discernible impact on the effectiveness of the learning model.